Edouard Manet ( 1832 - 1883 ) : The First of the Moderns . - Neret, Gilles (Koln Taschen, 2003)
<div id="vendorPoweredCoupon_feature_div" class="celwidget" data-feature-name="vendorPoweredCoupon" data-csa-c-type="widget" data-csa-c-content-id="vendorPoweredCoupon" data-csa-c-slot-id="vendorPoweredCoupon_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="5evxla-laa0gn-58b4v8-i6epbz" data-cel-widget="vendorPoweredCoupon_feature_div" style="box-sizing: border-box; color: rgb(15, 17, 17); font-family: "Amazon Ember", Arial, sans-serif; font-size: 14px;"> <div id="persistentWidget_feature_div" class="celwidget" data-feature-name="persistentWidget" data-csa-c-type="widget" data-csa-c-content-id="persistentWidget" data-csa-c-slot-id="persistentWidget_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="bmr6rb-wwjc1t-pnclbt-oev30b" data-cel-widget="persistentWidget_feature_div" style="box-sizing: border-box; color: rgb(15, 17, 17); font-family: "Amazon Ember", Arial, sans-serif; font-size: 14px;"><div id="b2bUpsell_feature_div" class="celwidget" data-feature-name="b2bUpsell" data-csa-c-type="widget" data-csa-c-content-id="b2bUpsell" data-csa-c-slot-id="b2bUpsell_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="2o2mt9-nh3qjb-batey3-hhzkvt" data-cel-widget="b2bUpsell_feature_div" style="box-sizing: border-box; color: rgb(15, 17, 17); font-family: "Amazon Ember", Arial, sans-serif; font-size: 14px;"><div id="applicablePromotionList_feature_div" class="celwidget" data-feature-name="applicablePromotionList" data-csa-c-type="widget" data-csa-c-content-id="applicablePromotionList" data-csa-c-slot-id="applicablePromotionList_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="puuahi-8nbt3b-cy6sbd-3ml9xk" data-cel-widget="applicablePromotionList_feature_div" style="box-sizing: border-box; color: rgb(15, 17, 17); font-family: "Amazon Ember", Arial, sans-serif; font-size: 14px;"><div id="globalStoreBadgePopover_feature_div" class="celwidget" data-feature-name="globalStoreBadgePopover" data-csa-c-type="widget" data-csa-c-content-id="globalStoreBadgePopover" data-csa-c-slot-id="globalStoreBadgePopover_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="ydsl72-t5grsx-k42te4-hjhsn2" data-cel-widget="globalStoreBadgePopover_feature_div" style="box-sizing: border-box; color: rgb(15, 17, 17); font-family: "Amazon Ember", Arial, sans-serif; font-size: 14px;"><div id="deepCheckPromise_feature_div" class="celwidget" data-feature-name="deepCheckPromise" data-csa-c-type="widget" data-csa-c-content-id="deepCheckPromise" data-csa-c-slot-id="deepCheckPromise_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="55my17-vwv1he-r37j7l-9cogwr" data-cel-widget="deepCheckPromise_feature_div" style="box-sizing: border-box; color: rgb(15, 17, 17); font-family: "Amazon Ember", Arial, sans-serif; font-size: 14px;"><div id="apEligibility_feature_div" class="celwidget" data-feature-name="apEligibility" data-csa-c-type="widget" data-csa-c-content-id="apEligibility" data-csa-c-slot-id="apEligibility_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="fupzoy-z8vub6-u7wvqi-sio1sl" data-cel-widget="apEligibility_feature_div" style="box-sizing: border-box; color: rgb(15, 17, 17); font-family: "Amazon Ember", Arial, sans-serif; font-size: 14px;"><div id="latestExtraProductInfoFeatureGroup" class="celwidget" data-feature-name="latestExtraProductInfoFeatureGroup" data-csa-c-type="widget" data-csa-c-content-id="latestExtraProductInfoFeatureGroup" data-csa-c-slot-id="latestExtraProductInfoFeatureGroup" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="kfw13c-4pe7pc-iwzoas-y4pizj" data-cel-widget="latestExtraProductInfoFeatureGroup" style="box-sizing: border-box; color: rgb(15, 17, 17); font-family: "Amazon Ember", Arial, sans-serif; font-size: 14px;"><div id="newerVersion_feature_div" class="celwidget" data-feature-name="newerVersion" data-csa-c-type="widget" data-csa-c-content-id="newerVersion" data-csa-c-slot-id="newerVersion_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="dhp5b5-9y5x67-u6udqa-fccky7" data-cel-widget="newerVersion_feature_div" style="box-sizing: border-box;"><div id="productAlert_feature_div" class="celwidget" data-feature-name="productAlert" data-csa-c-type="widget" data-csa-c-content-id="productAlert" data-csa-c-slot-id="productAlert_feature_div" data-csa-c-asin="3822819492" data-csa-c-is-in-initial-active-row="false" data-csa-c-id="ymp50y-i8mcbx-bdonxk-cn9kzb" data-cel-widget="productAlert_featur
Keywords: Manet, Edouard, 1832-1883